How does the impact of a community trial on cardio-metabolic risk factors differ in terms of gender and living area? Findings from the Isfahan healthy heart program - Nizal Sarrafzadegan; Roya Kelishadi; Mansour Siavash; Gholamhossein Sadri; Hossein Malekafzali; Masoud Pourmoghaddas; Shahin Shirani; Maryam Boshtam; Sedigheh Asgary; Noushin Mohammadifard; Ahmad Bahonar; Babak Eshrati; et al. (Journal of Research in Medical Sciences, 2012)
Objective: To assess the impact of gender and living area on cardiovascular risk factors in the context of a comprehensive lifestyle intervention program. Design: Data from independent sample surveys before (2000--2001) and after (2007) a community trial, entitled the Isfahan Healthy Heart Program (IHHP) were used to compare differences in the intervention area (IA) and reference area (RA) by gender and living area. Setting: The interventions targeted the population living in Isfahan and Najaf-Abad counties as IA and Arak as RA. Participants: Overall, 12 514 individuals who were more than 19 years of age were studied at baseline, and 9570 were studied in postintervention phase. Interventions: Multiple activities were conducted in connection with each of the four main strategies of healthy nutrition, increasing physical activity, tobacco control, and coping with stress. Main Outcomes: Comparing serum lipids levels, blood pressure, blood glucose and obesity indices changes between IA and RA based on sex and living areas during the study. Results: In IA, while the prevalence of hypertension declined in urban and rural females (P < 0.05). In IA, the prevalence of hypercholesterolemia and hypertriglyceridemia decreased in both females and males of urban and rural areas except for hypercholesterolemia in rural males (P < 0.01). In RA, the significant changes include both decrease in the hypercholesterolemia among rural males (P < 0.001) and hypertriglyceridemia in urban females (P < 0.01), while hypertriglyceridemia was significantly increased in rural females (P < 0.01). Conclusions: This comprehensive community trial was effective in controlling many risk factors in both sexes in urban and rural areas. These findings also reflect the transitional status of rural population in adopting urban lifestyle behaviors.